Superior Carrier Lifetimes Exceeding 6 µs in Polycrystalline Halide Perovskites - Yang, Xiaoyu; Fu, Yunqi; Su, Rui; Zheng, Yifan; Zhang, Yuzhuo; Yang, Wenqiang; Yu, Maotao; Chen, Peng; Wang, Yanju; Wu, Jiang; Luo, Deying; Tu, Yongguang; et al. (Advanced materials (Weinheim), 2020)
Lead halide perovskite films have witnessed rapid progress in optoelectronic devices, whereas polycrystalline heterogeneities and serious native defects in films are still responsible for undesired recombination pathways, causing insufficient utilization of photon‐generated charge carriers. Here, radiation‐enhanced polycrystalline perovskite films with ultralong carrier lifetimes exceeding 6 μs and single‐crystal‐like electron–hole diffusion lengths of more than 5 μm are achieved. Prolongation of charge‐carrier activities is attributed to the electronic structure regulation and the defect elimination at crystal boundaries in the perovskite with the introduction of phenylmethylammonium iodide. The introduced electron‐rich anchor molecules around the host crystals prefer to fill the halide/organic vacancies at the boundaries, rather than form low‐dimensional phases or be inserted into the original lattice. The weakening of the electron‐phonon coupling and the excitonic features of the photogenerated carriers in the optimized films, which together contribute to the enhancement of carrier separation and transportation, are further confirmed. Finally the resultant perovskite films in fully operating solar cells with champion efficiency of 23.32% are validated and a minimum voltage deficit of 0.39 V is realized. Ultralong charge‐carrier lifetimes >6 μs are achieved in polycrystalline halide perovskites by decorating the grain boundaries with a trace amount of electron‐rich anchors, which benefits from weak excitonic effects and the weakening of electron–phonon couplings in passivated films, fulfilling reduced voltage deficits and enhanced efficiencies in perovskite photovoltaics. This finding provides a new insight into realizing superior carrier properties of polycrystalline perovskite films and high‐performance perovskite optoelectronics.